The effects of dithiaden on nitric oxide production by RAW 264.7 cells - Králová, Jana (Slovak Toxicology Society SETOX, 2008)
As reported in our previous studies, dithiaden (an antagonist of histamine H(1)-receptor, used clinically as an anti-allergic or anti-emetic drug) in a concentration range of 5×10(−5)–10(−4) M decreased the production of reactive oxygen species by phagocytes. In this study we investigated the influence of dithiaden on nitric oxide (NO) production by LPS-stimulated macrophages. The cell viability in the presence of 10(−4)–5×10(−5) M dithiaden was evaluated by an ATP-test. RAW 264.7 cells (2.5×10(6)/well) were preincubated with dithiaden for 60 mins and subsequently stimulated with 0.1 µg/ml of bacterial lipopolysaccharide. After incubating for 24 hours the NO production was determined spectrophotometrically using Griess reaction as a concentration of nitrites (the end product of NO metabolism) accumulated in the cell supernatants. The expression of inducible nitric oxide synthase (iNOS) in cell-lysates was evaluated using Western blot analysis. Scavenging properties of dithiaden against NO were evaluated amperometrically. Our data demonstrate that dithiaden in the concentration of 5×10(−5) M (approved by ATP test as non toxic) caused a significant decrease in the accumulation of nitrites, and in addition, this decline was followed by a marked reduction of iNOS protein expression. Amperometrical analysis did not show any scavenging properties of dithiaden against NO. From this data it can be suggested that the inhibition effect of dithiaden on macrophage NO production is caused exclusively by the suppression of iNOS protein expression.